As junções de palavras no português brasileiro cantado: estudos para uma aplicação - Starling, Juliana [UNESP]; Herr, Martha [UNESP] (Univ Federal Goias, 2012)
This article is a reflection on the possibilities for the linking and or connection of words in Brazilian Portuguese lyric diction with the intention of contributing this as a tool for singers, singing and diction teachers working with BP. The proposal came from a study of the norms for the Brazilian Portuguese pronunciation 1938 and 1958 rules, which addressed the issue, in conjunction with the analysis of the current norms, published in 2007.
The linking of words in brazilian portuguese liric diction: studies for an application
Keywords: Brazilian Portuguese; Lyric diction; Connecting words; Brazilian Portuguese pronunciation